Dissolved storage glycans shaped the community composition of abundant bacterioplankton clades during a North Sea spring phytoplankton bloom - Sidhu, Chandni; Kirstein, Inga V.; Meunier, Cédric L.; Rick, Johannes; Fofonova, Vera; Wiltshire, Karen H.; Steinke, Nicola; Vidal-Melgosa, Silvia; Hehemann, Jan-Hendrik; Huettel, Bruno; Schweder, Thomas; Fuchs, Bernhard M.; et al. (Microbiome, 2023)
Background Blooms of marine microalgae play a pivotal role in global carbon cycling. Such blooms entail successive blooms of specialized clades of planktonic bacteria that collectively remineralize gigatons of algal biomass on a global scale. This biomass is largely composed of distinct polysaccharides, and the microbial decomposition of these polysaccharides is therefore a process of prime importance. Results In 2020, we sampled a complete biphasic spring bloom in the German Bight over a 90-day period. Bacterioplankton metagenomes from 30 time points allowed reconstruction of 251 metagenome-assembled genomes (MAGs). Corresponding metatranscriptomes highlighted 50 particularly active MAGs of the most abundant clades, including many polysaccharide degraders. Saccharide measurements together with bacterial polysaccharide utilization loci (PUL) expression data identified β -glucans (diatom laminarin) and α -glucans as the most prominent and actively metabolized dissolved polysaccharide substrates. Both substrates were consumed throughout the bloom, with α -glucan PUL expression peaking at the beginning of the second bloom phase shortly after a peak in flagellate and the nadir in bacterial total cell counts. Conclusions We show that the amounts and composition of dissolved polysaccharides, in particular abundant storage polysaccharides, have a pronounced influence on the composition of abundant bacterioplankton members during phytoplankton blooms, some of which compete for similar polysaccharide niches. We hypothesize that besides the release of algal glycans, also recycling of bacterial glycans as a result of increased bacterial cell mortality can have a significant influence on bacterioplankton composition during phytoplankton blooms. A8iwHBb1oEC4q82u7HbzQ4 Video Abstract